Correlation between Hertel exophthalmometric value and refraction in young Cameroonian adults aged 20 to 40 years - Dohvoma VA (Clinical Ophthalmology, 2016)
Viola A Dohvoma, Emilienne Epée, Stève R Ebana Mvogo, N Sandra Lietcheu, Côme Ebana Mvogo Department of Ophthalmology, Faculty of Medicine and Biomedical Sciences, University of Yaoundé I, Yaoundé, Cameroon Purpose: To study the relationship between exophthalmometric value (EV) and refractive error in Cameroonian young adults.Patients and methods: A prospective descriptive study was carried out in the ophthalmic unit of the Yaoundé Central Hospital from March to May 2015. Consenting patients aged 20–40 years with no intraocular pathology who were seen for refractive errors were included. Ocular protrusion was measured using the Hertel exophthalmometer. Automatic refraction was done following cycloplegia with cyclopentolate and tropicamide.Results: A total of 200 patients were included (68% females and 32% males). The mean age was 27.2±6 years. Hyperopia was the most common refractive error (51%), followed by hyperopic astigmatism (19.3%). EV varied between 9 mm and 23 mm, with a mean of 14.8±2.5 mm in the right eye and 15.0±2.5 mm in the left eye. The mean EVs were 17.10±2.80 mm in myopia, 14.24±1.92 mm in hyperopia, 16.72±2.58 mm in myopic astigmatism, 14.07±2.19 mm in hyperopic astigmatism, and 14.77±2.40 mm in mixed astigmatism. The spherical value had a negative correlation with EV (P=0.0000).Conclusion: The mean EV of this Cameroonian population is smaller than that of other populations and is consistent with the known characteristic hyperopic status of the population. A study on a larger sample will determine the normative data of absolute and relative EV in our setting. Keywords: refractive error, exophthalmometry, Cameroon